CDR2 and CDR2L line blot performance in PCA-1/anti-Yo paraneoplastic autoimmunity - Vorasoot, Nisa; Scharf, Madeleine; Miske, Ramona; Thakolwiboon, Smathorn; Dubey, Divyanshu; Mills, John R.; Pittock, Sean J.; Zekeridou, Anastasia; Ott, Anthonina; McKeon, Andrew (Frontiers in Immunology, 2023)
N.Vorasoot reports no disclosures relevant to the manuscript. M Scharf is employed by Euroimmun. R. Miske is employed by Euroimmun. S.J. Pittock is a named inventor on filed patents that relate to functional AQP4/NMO-IgG assays and NMO-IgG as a cancer marker, has patents pending for KLHL11-IgG and Septin-5-IgG, and issued for MAP1B-IgG as markers of neurologic autoimmunity and paraneoplastic disorders, has consulted for Alexion and Medimmune; and has received research support from Genentech, Grifols, Medimmune, and Alexion; S. Thakolwiboon reports no disclosures relevant to this manuscript. D. Dubey has research support from Department of Defence (CA210208 & PR220430) and UCB, has consulted for UCB, Immunovant, Argenx and Astellas pharmaceuticals (compensation for consulting activities paid directly to Mayo Clinic), and has patent licensed for KLHL11-IgG, and patents pending for LUZP4-IgG and cavin-4-IgG as markers of neurological autoimmunity; JR Mills reports no disclosures relevant to the manuscript. A. Zekeridou has patent applications pending on PDE10A-IgG and DACH1-IgG as biomarkers of paraneoplastic neurological autoimmunity and has received research funding from Genentech not relevant to this study. Has consulted without personal compensation for Alexion Pharmaceuticals; Anthonina Ott is employed by Euroimmun. A.